2001
DOI: 10.1007/s00259-001-0698-9
|View full text |Cite
|
Sign up to set email alerts
|

CT vs 68Ge attenuation correction in a combined PET/CT system: evaluation of the effect of lowering the CT tube current

Abstract: With the introduction of combined positron emission tomography/computed tomography (PET/CT) systems, several questions have to be answered. In this work we addressed two of these questions: (a) to what value can the CT tube current be reduced while still yielding adequate maps for the attenuation correction of PET emission scans and (b) how do quantified uptake values in tumours derived from CT and germanium-68 attenuation correction compare. In 26 tumour patients, multidetector CT scans were acquired with 10,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(74 citation statements)
references
References 4 publications
3
68
0
3
Order By: Relevance
“…It has previously been shown that this reduction in mA gives CT scans which are adequate for attenuation correction [10]. Each patient was asked to hold his/her breath at normal end-inspiration for about 10 to 15 seconds (depending on their height) for the first low dose CT scan, then at normal end-expiration for the second CT scan and finally at roughly mid-volume between end-expiration and end-inspiration for the third scan.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…It has previously been shown that this reduction in mA gives CT scans which are adequate for attenuation correction [10]. Each patient was asked to hold his/her breath at normal end-inspiration for about 10 to 15 seconds (depending on their height) for the first low dose CT scan, then at normal end-expiration for the second CT scan and finally at roughly mid-volume between end-expiration and end-inspiration for the third scan.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…Taking into consideration the CT system used in the present study and the specific imaging technique of integrated PET/CT, the CT images evaluated have a lower image quality than could be expected if a standalone spiral CT or multislice CT were to be used. The CT part of the integrated PET/CT was performed with a lower dose (80 versus 120 mA for a dedicated chest CT in the Dept of Radiology, University Hospitals Gasthuisberg, Leuven, Belgium) [23]; however, HANY et al [24] compared different CT doses and found no significant differences in accuracy when 80 mA was used compared with that of a dedicated chest CT. The CT was performed at normal expiratory breath-hold (limited breath-hold technique) versus at deep inspiration for a dedicated chest CT.…”
Section: Value Of Integrated Pet/ct W De Wever Et Almentioning
confidence: 99%
“…Kamel et al [13] reported that the CT tube current can be reduced while still yielding adequate attenuation correction of PET scans, and CT tube currents in the range 10-120mA yielded the same values for FDG uptake or lesion size. Therefore, they showed that the very low CT tube current is sufficient if the CT scan is only used for attenuation correction.…”
Section: Discussionmentioning
confidence: 99%
“…However, the linear attenuation coefficients in the range 10-40mA yielded significant differences in the 500-mm obese patient simulated phantom. These finding indicated that an error in line attenuation coefficients in CT-based attenuation correction were most likely to have been caused by the much larger phantom size and a variety of CT scan-specific parameters [13,14], such as tube voltage (kVp), tube current (mA) and rotation time (s).…”
Section: Discussionmentioning
confidence: 99%